Poststreptococcal reactive arthritis: clinical course and outcome in 15 patients - Koçak, Gülendam; İmamoğlu, Ayten; Tutar, Hasan Ercan; Atalay, Semra; Türkay, Sadi (The Turkish Journal of Pediatrics, 2000)
Patients with Group A beta-hemolytic streptococcal infection and articular disease, who do not fulfill the modified Jones criteria for diagnosis of acute rheumatic fever (ARF), have been classified as having poststreptococcal reactive arthritis (PSRA). We reviewed the clinical characteristics, laboratory findings and outcome of 15 patients with PSRA. None of these patients had clinical evidence of carditis. The pattern of joint involvement was variable and included arthritis in five patients and arthralgia in the remaining ten patients. Nine patients were treated with salicylates for one to 16 weeks; the others recovered spontaneously. Usually, the patients with arthralgia responded promptly to salicylates, while the response was poor in patients with arthritis. One patient with monoarthritis developed carditis nine months after his first arthritis attack. Another patient presenting with monoarthritis later had two additional episodes of poststreptococcal reactive arthralgia.It seems there is a wide spectrum of poststreptococcal rheumatic diseases, and patients with PSRA are also at risk for cardiac disease; therefore, prophylactic antibiotic therapy should be considered in these patients.
Keywords: poststreptococcal reactive arthritis/arthralgia; childhood